The International Workshop: Local Tsunami Warning and Mitigation, Petropavlovsk-Kamchatsky, Russia, September, 2002;proceedings (Janus-K, 2002)
In commemoration of the 50th anniversary of the 1952 great Kamchatka earthquake and tsunami Incl. bibl. Sponsored by IOC